Explicit finite-element analysis for the in-plane cyclic behavior of unreinforced masonry structures. - Karapitta, Lucia
A simple constitutive model is proposed for an in-plane numerical analysis of unreinforced masonry structures, which are subject to cyclic loading, by using explicit dynamic procedures. The proposed model is implemented by using two-dimensional plane-stress finite elements. Three different constitutive relations that are based on the total strain in the global material system are used. Cracking and crushing are controlled through normal strains, whereas shear is controlled through shear strain. Separate hysteretic rules are adopted for each mode of damage. A numerical analysis of masonry walls that are subject to cyclic loading has demonstrated that the use of explicit procedures in conjunction with the proposed model results in an acceptable accuracy when compared with the experimental results.
Keywords: Unreinforced masonry wall; Explicit dynamic; Smeared-crack model; Hysteretic response